Static Postural Stability in Chronic Ankle Instability, an Ankle Sprain and Healthy Ankles - Kwon, Yong Ung (International Journal of Sports Medicine, 2018)
To identify the single leg balance (SLB) test that discriminates among healthy, coper, and chronic ankle instability (CAI) groups and to determine effects of ankle muscles on the balance error scoring system (BESS) among the three populations. 60 subjects (20 per group) performed the SLB test with eyes open (EO) and eyes closed (EC). Normalized mean amplitude (NMA) of the tibia anterior (TA), fibularis longus (FL), and medial gastrocnemius (MG) muscles and BESS were measured while performing the SLB test. The coper group had a lower error score than the CAI group in the EC. NMA was greater in the CAI group compared to in the healthy and coper groups regardless of muscle type. NMA of the TA was less than the PL and MG regardless of the group in the EO. The CAI group demonstrated greater NMAs of the PL and MG than the healthy and coper groups in the EC. The CAI group demonstrated greater NMA of the PL and MG by compensating their ankle muscles in the EO and EC. BESS suggests that the coper group may have coping mechanisms to stabilize static postural control compared to the CAI group. The EC may be better to detect static postural instability in the CAI or coper group.
Keywords: single-leg balance test; electromyography; balance error scoring system; mean amplitude; eyes open; eyes closed